Differing Mechanisms of New Particle Formation at Two Arctic Sites. Issue 4 (20th February 2021) - Beck, Lisa J.; Sarnela, Nina; Junninen, Heikki; Hoppe, Clara J. M.; Garmash, Olga; Bianchi, Federico; Riva, Matthieu; Rose, Clemence; Peräkylä, Otso; Wimmer, Daniela; Kausiala, Oskari; Jokinen, Tuija; et al.
Abstract: New particle formation in the Arctic atmosphere is an important source of aerosol particles. Understanding the processes of Arctic secondary aerosol formation is crucial due to their significant impact on cloud properties and therefore Arctic amplification. We observed the molecular formation of new particles from low‐volatility vapors at two Arctic sites with differing surroundings. In Svalbard, sulfuric acid (SA) and methane sulfonic acid (MSA) contribute to the formation of secondary aerosol and to some extent to cloud condensation nuclei (CCN). This occurs via ion‐induced nucleation of SA and NH3 and subsequent growth by mainly SA and MSA condensation during springtime and highly oxygenated organic molecules during summertime. By contrast, in an ice‐covered region around Villum, we observed new particle formation driven by iodic acid but its concentration was insufficient to grow nucleated particles to CCN sizes. Our results provide new insight about sources and precursors of Arctic secondary aerosol particles. Plain Language Summary: Cloud properties are sensitive to the formation of new aerosol particles in the Arctic atmosphere, yet little is known about the chemistry and processes controlling this phenomenon. Here, based on comprehensive in situ measurements, we identify the very first steps of atmospheric new particle formation, that is, formation of small clusters from compounds present in the gas phase, and candidates for the subsequent growth of these clusters to larger sizes, at two Arctic sites: one surrounded by open waters, the other one by sea ice. We show how environmental differences affect secondary aerosol formation via emissions and atmospheric chemistry of aerosol precursor gases. Our results provide previously unidentified insight into how future changes in the Polar environment could be reflected in the chain of processes linking the Arctic biosphere and cryosphere to atmospheric aerosol particles, clouds, and climate. Key Points: Secondary aerosol formation studied at two sites in the atmosphere of the high Arctic In situ measurements observing precursor gases and further following the growth of particles up to cloud condensation nuclei sizes We observed significant differences of new particle formation above open ocean versus sea ice surroundings